Advantages of green technology - Banerjee, Sanjukta; Akuli, Krishna (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Green technology implies to a system that uses innovative methods to create environment friendly products. Mainly, it comprises of various everyday cleaning products, energy sources, inventions, waste, clothing and a host of others. Going green or using technologies that are friendly to the environment is among the many ways that countries are looking into in order to spur economic growth and improve the lives of its citizens. Green technology uses renewable natural resources that never depletes. Green technology uses new and innovative energy generation techniques. Green nanotechnology that uses green engineering and green chemistry is one of the latest in green technologies. One of the important factors for environmental pollution is the disposal of waste. Green technology has answers to that as well. It can effectively change waste pattern and production in a way that it does not harm the planet and we can go green. Among the possible areas where these creations and growth are expected to come from include green energy, organic agriculture, eco-friendly textiles, green building constructions, and manufacturing of related products and materials to support green business. Because this is but new to the industry, it is also expected to attract new customers who will see the many advantages of using green technologies in their homes and others. Besides other forms of green technology in field of generation of energy are done by solar power and fossil fuel. These have no adverse effect on the planet and it won’t replenish. So future generation can also benefit from them without harming the planet. This paper focuses on the advantages of green technology and the benefits that can be accrued out of it. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>